Tuberculosis: Development of New Drugs and Treatment Regimens - Soedarsono Soedarsono (Faculty of Medicine Universitas Airlangga, 2021)
Tuberculosis (TB) still becomes a public health crisis. Drug-resistant TB (DR-TB) becomes a concern as the increasing DR-TB cases in countries with high TB burden. The 2017 World Health Organization (WHO) guideline recommended a combination of TB treatment consisting of 2 months of intensive phase with isoniazid (H), rifampisin (R), pyrazinamid (Z), and ethambutol (E), followed by 4 months of continuation phase with HR daily. WHO has updated DR-TB treatment guidelines several times. In 2016, WHO recommended shorter regimen and individual regimen based on certain conditions. The most updated 2020 WHO guideline recommended the short regimen consisting of all oral drugs as well as changes in the grouping of medicines used in DR-TB regimens in longer/individual regimens. Bedaquiline, delamanid, pretomanid, and sutezolid are new drugs which have been studied for their uses as anti-TB drugs (ATD). Bedaquilin and delamanid, which have passed phase 3 trials, have been approved and recommended by WHO for DR-TB treatment. Repurposed drugs have been used for DR-TB treatment during the time of evaluation of drugs list and regimens for DR-TB treatment. Fluoroquinolones, clofazimine, linezolid, carbapenem, amoxicillin/clavulanic acid are repurposed drugs. TB and DR-TB management will be updated at any time, based on the latest findings in studies, to evaluate and improve the effectiveness of current treatments. Prevention of active TB disease by the treatment of latent TB infection (LTBI) is also a critical component of the end TB strategy by WHO. Therefore, the development of new drugs for the LTBI treatment is also needed.